Over-representation of construction-related occupations in male patients with systemic sclerosis. Issue 10 (29th May 2008) - Smith, V; Vanthuyne, M; Vander Cruyssen, B; Van Praet, J; Vermeiren, F; Smets, H; Houssiau, F; De Keyser, F
Abstract : Aims: Based on preliminary observations, we tested the hypothesis that construction-related occupations are associated with systemic sclerosis (SSc). Methods: The professional occupation of 91 patients with SSc (71 females and 20 males) was recorded. Categorisation into construction-related and other professions was performed. A double definition was used for construction-related occupations. The first (limited) definition was based upon categories of the Belgian National Institute of Statistics (NIS) occupational list. The following occupations were considered construction-related: electricians, joiners, masons and tilers, plumbers and pipefitters. The use of this list also allows us to compare the distribution of professions in these patients with that in the general population. As the NIS occupational list is limitative and leaves out some "real-life" construction-related occupations, a second and broader interpretation was given to the concept of construction-related occupations. Results: The prevalence of construction-related professions in males with SSc, according to the limited definition, was 10-fold higher than in the general working population (50% vs 5%; p<0.001). Interestingly, most of the patients with construction-related occupations were electricians. In the broader interpretation, 75% of the men with SSc fell into the category of construction-related occupations. Conclusions: The data show an association between SSc and professional occupation.